Effect of gamma ray irradiation doses on pollen viability and in-vitro germination in Citrus - KUNDU, MANOJ; DUBEY, ANIL; MALIK, S K (The Indian Journal of Agricultural Sciences, 2016)
Induction of haploid plants in fruit crops through gamma irradiated pollen technique is of paramount importance in modern fruit breeding to reduce the breeding cycle. But the major problem of this technique is the sensitivity of pollen grains to higher irradiation doses. Present work analyzed the viability, in vitro germinability and pollen tube growth of gamma ray irradiated pollens of 2 different Citrus species: C. limetta, and C. sinensis. Both viability and in vitro germination capacity of irradiated pollen decreased gradually with increasing concentrations of irradiation inboth the pollen parent; however, at highest irradiation dose (400 Gy), reduction of pollen viability and in vitro germination capacity, as compared to respective controls was recorded minimum in C. limetta (11.07 and 29.78%, respectively). In vitro pollen tube length as measured at 24, 48 and 72 hr after incubation, was found maximum in C.limetta (267.83, 303.24 and 325.57 Î¼m, respectively). Our experiment revealed that pollen of C. limetta has higher resistance to gamma ray irradiation as compared to C. sinensis, hence C. limetta can be employed as more reliable pollen parent in haploidy programme of Citrus.